Використання молекулярно-біохімічних марекерів метаболізму кісткової тканини при скринінгу стоматологічного здоров'я в населення - Сидоренко, Олександр Олександрович; Павлов, Сергій Васильович; Возний, Олександр Вікторович; Sydorenko, O. O.; Pavlov, S. V.; Voznyi, O. V. (My University, 2020)
Запровадження в комплекс профілактичних оглядів стоматологічних пацієнтів біологічних маркерів – актуальне завдання сучасної стоматології й клінічної лабораторної діагностики. Особливе значення воно має для стоматологічних пацієнтів, які живуть/працюють під впливом шкідливих хімічних факторів. Проведено комплексне вивчення вмісту лактоферину, кателіцидину й MMP8 у ротовій рідині 50 пацієнтів, що працювали в шкідливих для здоров’я умовах (1 група), і 50 пацієнтів, характер праці яких не пов'язаний зі шкідливою дією хімічних факторів (2 група). Дослідженнями встановлено, що в пацієнтів, праця яких пов’язана із впливом шкідливих хімічних факторів, інтенсивніше відбуваються патологічні процеси в ротовій порожнині, а ушкодження тяжчі, ніж у пацієнтів, умови праці яких безпечні. Ці патологічні процеси спостерігаються на тлі виражених патобіохімічних процесів у ротовій рідині (значне підвищення лактоферину й ММР8 на тлі зниження концентрації кателіцидину). At present, the research interests of both dentists and clinical laboratory diagnosticians lie in the field of using oral fluid as an object of diagnostic estimation of molecular and biochemical markers in oral cavity diseases. It is commonly known that oral fluid has both organic and non-organic components. Non-organic components of saliva are represented by macro- and microelements that can be parts of various compounds or stay in the ionized form. Organic components are represented by proteins, carbohydrates, lipids, essential nitrogenous compounds (urea and uric acid), vitamins, hormones, organic and nucleic acids. Compared with the traditional method of blood testing, the identification of markers in the oral fluid has several advantages. They are non-invasiveness, atraumatic character for the patient, the absence of stress typical of venipuncture; simpler conditions of storage and transportation due to the liquid state (unlike whole blood, which tends to coagulate); being able to take biological material an unlimited number of times; no need for qualified personnel and special equipment when taking oral fluid. The introduction of biological markers into the complex of dental checkups is one of the topical tasks of modern dentistry and clinical laboratory diagnostics. This is particularly important for those dental patients whose living or working conditions are accompanied by harmful chemical factors. The authors have performed complex research of lactoferrin, cathelicidin, and MMP8 present in the oral fluid of 50 patients who worked under harmful conditions (group 1), and of other 50 patients whose work is not associated with the harmful influence of chemical factors (group 2). The oral fluid was collected on an empty stomach in the morning by spitting into a sterile glass tube. The biomass was centrifuged and stored at 300C, and the amount of lactoferrin (Hycto Biotech, the Netherlands), cathelicidin (Hycult Biotech, the Netherlands), and MMP8 (Matrix Metalloproteinase-8) was determined in the test samples. The analysis was performed by enzyme- linked immunosorbent assay based on the use of a "sandwich" variant of solid-phase enzyme-linked immunosorbent assay. The procedure was performed on the enzyme-linked immunosorbent assay ImmunoChem- 2100 (USA). The analysis was performed in 96-well microplates, the bottom of the wells was covered with monoclonal antibodies to the corresponding molecular marker.
The use of molecular and biochemical markers of bone metabolism for screening of dental health of the population
Keywords: лактоферин; кателіцидин; MMP8; ротова рідина; пацієнти, які працюють у шкідливих для здоров’я умовах; lactoferrin; cathelicidin; oral fluid; patients working under harmful conditions